Study of English Reading Teaching Strategies in Senior High School based on Cognitive Load Theory - Sun, Qingling (International Journal of Social Sciences and Public Administration, 2024)
This study first explores the feasibility of applying cognitive load theory to high school English reading teaching by defining core concepts such as cognitive load and schema, combining with the current situation of middle school English reading learning and the current English core literacy and curriculum objectives. The main part of the study starts from the three elements under the cognitive load theory, and combined with the teaching design practice of Unit 1 The Monarch’s Jourey of FLTRP Edition, the final aim is to further integrate and explore the classroom teaching strategies of middle school English reading based on the cognitive load theory, emphasizing the student-centered approach. To promote students’ efficient schema construction and reading comprehension automation, create a better English reading learning environment, help students improve reading skills, and get closer to the goal of middle school English teaching.